Islamic Banks in Morocco: Facts and Challenges - Fakhri, Lamiae; Lazrak, Yassir; Trid, Sabah (IAIN Kudus, 2023)
Though the global financial crisis has strongly challenged the development models of conventional finance, currently the participatory financial industry, known as